Consumer price sensitivity in Dutch health insurance - van Dijk, Machiel (Springer US, 2008)
Aim To estimate the price sensitivity of consumer choice of health insurance firm. Method Using paneldata of the flows of insured between pairs of Dutch sickness funds during the period 1993–2002, we estimate the sensitivity of these flows to differences in insurance premium. Results The price elasticity of residual demand for health insurance was low during the period 1993–2002, confirming earlier findings based on annual changes in market share. We find small but significant elasticities for basic insurance but insignificant elasticities for supplementary insurance. Young enrollees are more price sensitive than older enrollees. Conclusion Competition was weak in the market for health insurance during the period under study. For the market-based reforms that are currently under way, this implies that measures to promote competition in the health insurance industry may be needed.